A multidisciplinary weight-loss program: the importance of psychological group therapy - Gustavo Duarte Ferrari; Milton Azevedo; Leonardo Medeiros; Carmem Beatiz Neufeld; Rosane Pilot Pena Ribeiro; Bernard Pimentel Rangé; Carlos Roberto Bueno Júnior
Abstract In addition to dietary factors and sedentary habits, there is a relationship between obesity and psychological variables, even without a clear distinction between cause, effect, and correlation. Despite this relationship, weight-loss programs are limited to a combination of nutrition and physical education, leaving psychological intervention out of the treatment plan. Self-esteem issues, depression, and anxiety are just some of the emotional conditions related to obesity. However, there is no information in the literature about the importance of psychological counseling in a multidisciplinary program for weight-loss in adults. In this context, the main objective of this study was to analyze the effect of cognitive-behavioral therapy in groups (CBTG) combined with nutrition and physical education within a multidisciplinary approach to treat obesity. 46 individuals (7 men and 39 women) were divided into two groups: control (GC) and psychology (GP). Baseline and intervention measures were obtained prior to intervention and before the final meeting, including physical capacity tests and the administering the International Physical Activities Questionnaire (IPAQ). Both groups attended weekly lectures given by a nutritionist and two physical education professionals for 12 weeks. In addition, the GP participated in weekly sessions of CBTG for the same period. After the program, there were significant changes in body mass index, waist circumference, body fat percentage, and strength of the lower limbs in both groups. In addition to these changes, the GP also showed improvements in diastolic blood pressure and IPAQ scores, being the only one that increased its time of weekly physical activity. Thus, it was concluded that the psychological treatment might play an important role in a multidisciplinary weight-loss program.